Demand for TV content in a national language: The case of Kazakhstan - Yessenbekova, Ulbossyn; Syzdykova, Aida; Kutym, Begim (International Journal of Innovative Research and Scientific Studies, 2024)
This study examines preferences in selecting television content, using a national television channel as a case study. The Russian language put a lot of pressure on the Kazakh language during the communist regime. Post-Kazakhstan’s independence, linguistic dynamics shifted as authorities began responding to the demands of the Kazakh-speaking population. The aim is to test the hypothesis regarding the increasing demand for native language content, supported by the analysis of TV program ratings. For hypothesis testing, we employed empirical data obtained through an investigation into the preferences of the Kazakh-speaking audience. A total of 300 residents in Astana, aged 20-70, were interviewed. The survey results elucidate the correlation between public events and the television audience’s preferences. Historical, complex, and comparative analyses were employed, utilizing empirical data derived from a television audience preference study. The examination of television projects and their scripts revealed that language format substantially influences content informativeness and viewership ratings. Findings highlight a correlation between major events and television audience preferences. Programs in the Kazakh language elicit a positive response from the country’s television audience, particularly when discussing engaging topics. Based on research, recommendations are offered for enhancing editorial policies on television channels, with an emphasis on incorporating more Kazakh-language projects to better cater to the growing demand.